The influence of work environment, employee personal values and reward program towards employee engagement among employees in Kedah state registration department - Rohasniza, Kamaludin (2023)
Employee engagement alludes the psychological state that impacts and individual emotional, physical, and cognitive involvement in their everyday employment duties and behaviours. The aim of this study is to examine the relationship of three independent variables which are work environment, employee personal values, and reward program towards the dependent variable which is employee engagement amongst employee in Kedah State Registration Department. The data collected through digital survey questionnaires from 158 respondents using the probability sampling technique. Employee Engagement Model and Rewards System Theory is used as the underpinning theory to support this study. Results shown that there was significant positive relationship between work environment, employee personal values, and reward program in the organization. This study helps organizations and employers to better understand employees focus and needs in their work engagement to achieve organization goals.